57.1k views
17 votes
3x -5x + 8x = 4x + 18

User Melly
by
5.5k points

2 Answers

9 votes

Answer:

-9

Explanation:

3x−5x+8x=4x+18

Step 1: Simplify both sides of the equation.

3x−5x+8x=4x+18

3x+−5x+8x=4x+18

(3x+−5x+8x)=4x+18(Combine Like Terms)

6x=4x+18

6x=4x+18

Step 2: Subtract 4x from both sides.

6x−4x=4x+18−4x

2x=18

Step 3: Divide both sides by 2.

2x

2

=

18

2

User William Gunawan
by
4.8k points
10 votes

Answer:

x = 9

Explanation:

6x = 4x + 18

6x - 4x = 18

2x = 18

x = 9

User WileyCoyote
by
4.8k points